Efectos de los agentes físicos en pacientes con patologías neurológicas del Centro Gerontológico de Babahoyo, periodo octubre 2024 - abril 2025 - Chamorro Pérez, Jeniffer Cristina (2025)
Physical agents play a fundamental role in the functional recovery of the musculoskeletal system after any injury or trauma. There is currently sufficient scientific evidence of the role that these techniques play in osteoarticular conditions. Even with all these previous investigations, the effects that this set of treatments offers when addressing neurological pathologies remain in doubt. This group of diseases has taken great interest within the health system since it is associated with generating dependency and disability in the elderly population where this type of chronic-degenerative pathologies predominate. Among them, cerebrovascular event, Parkinson's, multiple sclerosis, etc. Physical agents in the area of physiotherapy are key to combat the symptoms that cause these diseases, contributing to pain relief, spasticity reduction, and muscle control. It is worth mentioning that among the physical agents is kinesiotherapy, which is responsible for body movement, becoming a fundamental pillar for the patient's recovery. It favors the neuroplasticity of the brain, where it generates new neural connections, with the aim of changing and adapting to the new ways of life that cause these pathologies. The present research study is entitled 'Effects of physical agents on patients with neurological pathologies at the Babahoyo gerontological center, period October 2024 - March 2025', its importance lies in analyzing the effects that physical agents have on these diseases considered disabling for a vulnerable population, older adults. To meet the objective, a non-experimental cross-sectional study was carried out, with a descriptive approach complementing two main types of research: documentary, focused on the review and analysis of existing information, and field research, aimed at direct data collection. The techniques applied included information collection, document review, application of surveys, and direct observation. The sample population consisted of 50 people and the work was done with a sample of 30 people.